Practices of using interviews in history of contemporary economics: A brief survey - Dorian Jullien (Duke University, Center for the History of Political Economy (CHOPE), 2018)
This paper discusses the similarities and differences in the plurality of practices regarding the use of interviews by historians of economics - i.e., either the use of someone else's interviews as sources or the use of interviews conducted by the historian for her or his work.
Keywords: B00; B20; B29; B30; B40; 330; history of economics; history of economic thought; historiography; oral history; interviews